The influence of match characteristics and experience on decision-making performance in AFL umpires. Issue 1 (January 2019) - Corrigan, Sean L.; Dwyer, Dan B.; Harvey, Briana; Gastin, Paul B.
Abstract: Objectives: The purpose of this study was to investigate the effects of match characteristics and elite level umpiring experience on the decision-making performance of umpires in the Australian Football League (AFL). Design: Cross Sectional Study. Methods: All decisions from the 2014 AFL home and away season made by 32 male AFL field umpires (age 33.1 ± 5.0 years, AFL umpire experience 122 ± 105 matches) were classified by a panel of four expert umpire coaches into correct, missed and unwarranted categories. The 8001 decisions were then further categorised based on the match time, score differential, field location, home ground advantage, match attendance and elite level umpiring experience. Chi-square with standardised residuals and two-way analysis of variance were used to analyse the data. Results: Higher elite level umpiring experience and a larger score differential at the time of the decision resulted in improved decision-making accuracy. Home ground advantage, attendance and match time did not influence the decision-making performance of umpires. Impact averse decisions occurred in the back line of play, with umpires tending to be conservative with decisions that may impact the score. Conclusions: Decisions that have an increased influence on an umpire's decision-making performance include score differential and elite umpiring experience. Implications on umpiring performance regarding the venue, attendance and the duration of a match were not apparent.